CLINICAL MANIFESTATION OF ORAL TUBERCULOSIS - Atik Kurniawati; Ni Made Mertaniasih; Mangestuti Agil (UNEJ e-Proceeding, 2016)
Tuberculosis (TB) is chronic infectious disease caused by Mycobacterium tuberculosis. According to WHO report, it infected almost one third people and Indonesia has been 5th position in the world. Tuberculosis is classified clinically as Pulmonary and Extra Pulmonary. Extra pulmonary tuberculosis can occur in the lymph nodes, meninges, kidneys, bone, skin and even oral cavity that we called oral tuberculosis. The oral tuberculosis may manifest in various form : ulcer, gingivitis, nodules, granulomatous, tuberculoma and osteomyelitis. The purpose of this paper to explain the clinical manifestation of oral tuberculosis.